The Religious Metaphysics of Vladimir Solovyov - Kojève, Alexandre (Springer International Publishing, 2018)
The original text of this work was published in the French journal Revue d'Histoire et de Philosophie Religieuses. This English translation presents Kojève's attempt to unify the religious philosophy of Vladimir Solovyov into a metaphysical system that Solovyov strived for but was never able to fully articulate in his lifetime.